Optimization of peel back force’s factor setting for sealing track with design of experiment - Danthaiwattana, Namkham; Wongthatsanekorn, Wuthichai (Thai Industrial Engineering Network Journal, 2017)
This article aims to find optimal setting of peel back force from seal track in integrated circuit industry by using the principles of design of experiment. Due to current process capability (Cpk) of peel back force was still out of specification and it had not passed requirements of the company. The analysis of parameters was performed using cause and effect matrix and failure mode and effects analysis. It was hypothesized that seven factors would influence to peel back force. Therefore, the experiments consisted of two steps. The first step of the experiment was screening to find the significant factors with fractional factorial design (27-1). The second step was to use significant factors to determine appropriate operating setting by performing (24) full factorials design. And optimization of peel back force’s factor setting for sealing track from four methods then select the method that most likely target. Work procedures were adjusted according to new appropriate parameter settings of each factor to establish new working standard along with setting training program. The result found that the Cpk increased to 1.98 which was higher than company target at 1.67.